Implementasi Sistem Terdistribusi Aplikasi Keuangan Brajasoft Asisten di SMPIT Ash- Shiddiiqi Jambi - Salsabila Tadya Hasibuan; Hetty Rohayani; Rico, Rico; Rahmi Handayani (LPPM Universitas Adiwangsa Jambi, 2023)
This research was created to find out the management system of Ash-Shiddiqi Junior HighSchool Jambi financemanagement and implementationof brojasoft financial software assistant used to managing the existing system of the school's finance management at Ash-Shiddiiqi Junior High School. The approach in this study is Research and Development (r&d). This study yielded results showing that in practice,Ash-Shidiiqi's data sustem is still based on the data system manual input, so in the process there are some challenges to the data processing and the school's recapulation of data. In a positive side can be found on the implementation of the brojasoft financial software of assistants in the school's financial information management process, the statement is strengthened by a better response than the respondents. There is a 93% line-to-deposit ratio based on the disbursement previously given to the NPLS. Using this modest presentation suggests that computerized software software or financial software software could be used as the school's financial administration software specifically atash-shiddiiqi junior high school jambi.